Novel 3D Magnetic Resonance Elastography for the Noninvasive Diagnosis of Advanced Fibrosis in NAFLD: A Prospective Study. (July 2016) - Loomba, Rohit; Cui, Jeffrey; Wolfson, Tanya; Haufe, William; Hooker, Jonathan; Szeverenyi, Nikolaus; Ang, Brandon; Bhatt, Archana; Wang, Kang; Aryafar, Hamed; Behling, Cindy; Valasek, Mark A; et al.
Abstract : OBJECTIVES: Recent studies show two‐dimensional (2D)‐magnetic resonance elastography (MRE) is accurate in diagnosing advanced fibrosis (stages 3 and 4) in nonalcoholic fatty liver disease (NAFLD) patients. Three‐dimensional (3D)‐MRE is a more advanced version of the technology that can image shear‐wave fields in 3D of the entire liver. The aim of this study was to prospectively compare the diagnostic accuracy of 3D‐MRE and 2D‐MRE for diagnosing advanced fibrosis in patients with biopsy‐proven NAFLD. METHODS: This cross‐sectional analysis of a prospective study included 100 consecutive patients (56% women) with biopsy‐proven NAFLD who also underwent MRE. Area under the receiver operating characteristic (AUROC) analysis was performed to assess the accuracy of 2D‐ and 3D‐MRE in diagnosing advanced fibrosis. RESULTS: The mean (±s.d.) of age and body mass index were 50.2 (±13.6) years and 32.1 (±5.0) kg/m 2, respectively. The AUROC for diagnosing advanced fibrosis was 0.981 for 3D‐MRE at 40 Hz, 0.927 for 3D‐MRE at 60 Hz (standard shear‐wave frequency), and 0.921 for 2D‐MRE at 60 Hz (standard shear‐wave frequency). At a threshold of 2.43 kPa, 3D‐MRE at 40 Hz had sensitivity 1.0, specificity 0.94, positive predictive value 0.72, and negative predictive value 1.0 for diagnosing advanced fibrosis. 3D‐MRE at 40 Hz had significantly higher AUROC ( P <0.05) than 2D‐MRE at 60 Hz for diagnosing advanced fibrosis. CONCLUSIONS: Utilizing a prospective study design, we demonstrate that 3D MRE at 40 Hz has the highest diagnostic accuracy in diagnosing NAFLD advanced fibrosis. Both 2D‐ and 3D‐MRE at 60 Hz, the standard shear‐wave frequency, are also highly accurate in diagnosing NAFLD advanced fibrosis.